Cortical diversity in three species groups of Parmotrema sensu lato (Parmeliaceae, lichenized Ascomycota) - Barbosa, Suzana Bissacot [UNESP]; Marcelli, Marcelo Pinto (Pergamon-Elsevier B.V. Ltd, 2010)
Conventional techniques for structural studies under light microscope were employed to describe and compare the upper cortex anatomy in three species groups of Parmotrema sensu lato. This study indicates that there is a pattern in the structure of the upper cortex in all the three groups of Parmotrema species studied here, and this pattern can be used to place each species group separately within the genus Parmotrema. Although the species of Parmotrema studied have palisade prosoplectenchymatous upper cortex, there are clear differences between the analyzed groups. The upper cortex of Parmotrema s. str. can be characterized by more elongated cells and very compressed hyphae with small interstices between them; the upper cortex of the species with reticular maculae is characterized by the presence of maculae produced by the organization of hyphae that rise towards to the upper cortex and that are not so compressed, while the upper cortex of the species with dimorphic rhizinae has less elongated almost-rounded cells without interstices or cracks but is generally accompanied by aeroplectenchyma. Besides, the first cell layer of the upper cortex presents differential staining by toluidine blue and the epicortex is tightly attached to it. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anatomy; Epicortex; Parmotrema; Upper cortex